2018
DOI: 10.3390/toxics6040071
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos- and Dichlorvos-Induced Oxidative and Neurogenic Damage Elicits Neuro-Cognitive Deficits and Increases Anxiety-Like Behavior in Wild-Type Rats

Abstract: The execution of agricultural activities on an industrial scale has led to indiscriminate deposition of toxic xenobiotics, including organophosphates, in the biome. This has led to intoxication characterized by deleterious oxidative and neuronal changes. This study investigated the consequences of oxidative and neurogenic disruptions that follow exposure to a combination of two organophosphates, chlorpyrifos (CPF) and dichlorvos (DDVP), on neuro-cognitive performance and anxiety-like behaviors in rats. Thirty-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 56 publications
(77 reference statements)
5
21
0
Order By: Relevance
“…Organophosphorus compounds are used for various military, household, and agricultural purposes to control and prevent different disease vectors such as flies, cockroaches, beetles, helminthes, cockroaches, termites, and corn rootworms [24]. Exposure to organophosphorus is strongly associated with the loss of cellular functions and the development of different diseases such as cardiovascular, renal, respiratory, and neurodegenerative disorders [25]. CPF is a wide-spectrum organophosphorus insecticide, and its indoor and outdoor uses cause several side effects to animals and humans [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organophosphorus compounds are used for various military, household, and agricultural purposes to control and prevent different disease vectors such as flies, cockroaches, beetles, helminthes, cockroaches, termites, and corn rootworms [24]. Exposure to organophosphorus is strongly associated with the loss of cellular functions and the development of different diseases such as cardiovascular, renal, respiratory, and neurodegenerative disorders [25]. CPF is a wide-spectrum organophosphorus insecticide, and its indoor and outdoor uses cause several side effects to animals and humans [24].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity metabolism, and its dysregulation causes different pathological conditions. CPF at different doses can inhibit AChE in different experimental models, leading to the accumulation of acetylcholine at synaptosomes and thus producing memory and learning impairments [7,25]. It has been demonstrated that CPF is able to inhibit AChE activity by enhancing the phosphorylation of its serine site [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hernández et al (2013) described that the pesticide mixture changes the toxicokinetics of the individual compounds, thus modifying their toxicity. Therefore, chemical interaction between two pesticides might be the reason for the antagonistic result (Imam et al 2018). Likewise, authors (Stepić et al 2013;Wang et al 2017) stated enhanced metabolization processes leading to faster excretion of metabolites, eventually resulting in decreased pesticide toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that CPF (2.5-20 mg/kg from postnatal days 27 to 36) produced depression-like behavioral signs when assessed one week following the last CPF dose [37]. Cognitive deficits along with anxiety traits were noted on days 10 and 14 of a two-week CPF (14.9 mg/kg) exposure paradigm [38]. Another study on behavioral toxicity of repeated CPF exposures showed that CPF (18 mg/kg daily for 14 days or every other day for 30 days) leads to increased impulsivity and reductions in attention when assessed during and up to 30 days post exposure [39,40].…”
Section: Introductionmentioning
confidence: 99%